The future of the international monetary system - Ansgar Belke; Kerstin Bernoth; Ferdinand Fichtner (DIW Economic Bulletin, 2011)
The financial crisis of 2007/2008 and the current Euro crisis challenge the current global monetary system. They drastically reveal the actual system's weaknesses und show the eminent importance of the international monetary system for the stability of markets and national economies. DIW Berlin was commissioned by the Federal Ministry of Finance to research possible alternatives to the existing exchange rate regime. In principle, neither of the two extremes - completely free or fixed exchange rates - is suitable. A mixed system is preferable - with improvements to the status quo, though. An exchange rate regime with few big currency areas, which are linked to each other with flexible exchange rates, should be the aim of reforms. This should correspond to a multi-polar key currency system with the currently dominating US Dollar and the Euro as well as the Chinese Renmimbi as most important actors. These developments should be accompanied by substantial improvements in the regulatory framework of the financial markets. Necessary elements are a reinforced global and especially European economic coordination and an internationally agreed-on, assertive financial market authority.
Keywords: E02; E42; F33; F42; F53; 330; international monetary system; key currency; exchange rate system; financial crisis; international economic policy